2004
DOI: 10.1038/nature03036
|View full text |Cite
|
Sign up to set email alerts
|

An obligate brood parasite trapped in the intraspecific arms race of its hosts

Abstract: Reciprocal selection pressures often lead to close and adaptive matching of traits in coevolved species. A failure of one species to match the evolutionary trajectories of another is often attributed to evolutionary lags or to differing selection pressures across a geographic mosaic. Here we show that mismatches in adaptation of interacting species--an obligate brood parasitic duck and each of its two main hosts--are best explained by the evolutionary dynamics within the host species. Rejection of the brood pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
56
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 24 publications
5
56
0
Order By: Relevance
“…Given this reduced parasitic virulence, one might expect somewhat benign interactions between the brood parasite and its hosts. However, our previous study in Argentina revealed that duck eggs are often rejected by the two main hosts, the red-gartered coot, Fulica armillata, and the redfronted coot, Fulica rufifrons (Figure 1), despite a lack of detectable costs of parasitism imposed by the ducks (Lyon & Eadie, 2004). Moreover, parasite and host eggs differ strikingly in appearance (Figure 2), yet an experimental study revealed that increasingly mimetic eggs do not alter rejection rates (Lyon & Eadie, 2004).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Given this reduced parasitic virulence, one might expect somewhat benign interactions between the brood parasite and its hosts. However, our previous study in Argentina revealed that duck eggs are often rejected by the two main hosts, the red-gartered coot, Fulica armillata, and the redfronted coot, Fulica rufifrons (Figure 1), despite a lack of detectable costs of parasitism imposed by the ducks (Lyon & Eadie, 2004). Moreover, parasite and host eggs differ strikingly in appearance (Figure 2), yet an experimental study revealed that increasingly mimetic eggs do not alter rejection rates (Lyon & Eadie, 2004).…”
mentioning
confidence: 99%
“…However, our previous study in Argentina revealed that duck eggs are often rejected by the two main hosts, the red-gartered coot, Fulica armillata, and the redfronted coot, Fulica rufifrons (Figure 1), despite a lack of detectable costs of parasitism imposed by the ducks (Lyon & Eadie, 2004). Moreover, parasite and host eggs differ strikingly in appearance (Figure 2), yet an experimental study revealed that increasingly mimetic eggs do not alter rejection rates (Lyon & Eadie, 2004). These paradoxical findings, coupled with the subsequent discovery of conspecific brood parasitism and rejection of conspecific parasitic eggs in both species of hosts, led us to conclude that the rejection of duck eggs is likely to be an incidental by-product of natural selection on hosts to recognize and reject the eggs of conspecifics (Lyon & Eadie, 2004).…”
mentioning
confidence: 99%
See 3 more Smart Citations